Triage for patients in ICUs during SARS-CoV-2 (COVID-19) - Salamoura (Μαρία Σαλαμούρα), Maria (Bioethica, 2020)
The SARS-CoV-2 virus has caused an unprecedented global pandemic in size, spread rate, severity and mortality. Humanity is facing a new challenge. The mass arrival of patients to hospitals with serious or even life-threatening illness has led to a reduction in the available medical equipment. Measures taken by the state are not enough to reduce the incidences of coronavirus. Additionally, the individual responsibility plays an important role in managing and dealing with the pandemic. The medical staff was often led to difficult decisions, such as which patients should be admitted to the ICU in a crisis period or how many patients need respiratory assistance. Such situations raise important bioethical issues, which we will study in more detail in this article.